PERBANDINGAN SARI KACANG KEDELAI DENGAN BUBUR UMBI BIT DAN KONSENTRASI SANTAN TERHADAP KARAKTERISTIK ES KRIM NABATI - Nana Sutisna Achyadi (Pasundan Food Technology Journal (PFTJ), 2020)
The purpose of this study was to determine the comparison of soybean milk with beetroot extract and concentrate of coconut milk on the characteristics of vegetable ice cream.This research method was conducted in two stages, namely preliminary research consist of analysis of total dissolved solids from the ratio of soybeans to water, namely (1: 4), (1: 6) and (1: 8). The primary research was carried out by using a 3x3 factorial system of randomized block design (RBD)/ Rancangan Acak Kelompok (RAK) with three repetitions. Factor (A) was comparison of soybean juice with beetroot porridge, consisting of 3 (three) levels a1 = 1: 1, a2 = 1: 2, a3 = 2: 1, and factor (B) was the use of coconut milk concentration, consisting of 3 (three ) level b1 = 18%, b2 = 20% and b3 = 22%. The results showed that the comparison of soybean milk with beetroot slurry influences fat content, overrun, melting time, and organoleptic tests including color, aroma and texture. Coconut milk concentration affects organoleptic test of texture attributes. The interaction between soybean juice comparison with beetroot extract and concentration of coconut milk on vegetable ice cream affected the organoleptic test of taste attributes but did not affect the fat content, protein content, overrun, melting time and organoleptic test of the color attributes, aroma and texture. The comparison of soybean juice with beetroot slurry influences fat content, overrun, melting time, and organoleptic tests including color, aroma and texture.